Efficacy of Ion-Channel Inhibitors Amantadine, Memantine and Rimantadine for the Treatment of SARS-CoV-2 In Vitro - Yuyong Zhou; Karen A. Gammeltoft; Andrea Galli; Anna Offersgaard; Ulrik Fahnøe; Santseharay Ramirez; Jens Bukh; Judith M. Gottwein (Viruses, 2021)
We report the in vitro efficacy of ion-channel inhibitors amantadine, memantine and rimantadine against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In VeroE6 cells, rimantadine was most potent followed by memantine and amantadine (50% effective concentrations: 36, 80 and 116 µM, respectively). Rimantadine also showed the highest selectivity index, followed by amantadine and memantine (17.3, 12.2 and 7.6, respectively). Similar results were observed in human hepatoma Huh7.5 and lung carcinoma A549-hACE2 cells. Inhibitors interacted in a similar antagonistic manner with remdesivir and had a similar barrier to viral escape. Rimantadine acted mainly at the viral post-entry level and partially at the viral entry level. Based on these results, rimantadine showed the most promise for treatment of SARS-CoV-2.